Nitrogen influence on suspended vs biofilm growth and resource recovery potential of purple non-sulfur bacteria treating fuel synthesis wastewater - S. Shaikh (17337769) (2023)
Purple non-sulfur bacteria (PNSB) have a strong potential for various bioproduct avenues including single-cell protein (SCP), and production of pigments and polyhydroxybutyrate. However, high substrate and separation costs are major barriers to commercialization. Therefore, this research investigates the integration of PNSB biomass production with treatment of fuel synthesis wastewater (FSW) for a low-cost substrate and formation of biofilm for improved harvesting. An enriched PNSB culture was cultivated in two different biofilm photobioreactors (nitrogen sufficient, N+, and nitrogen-deficient, N-) with a piece of woven agricultural shade cloth as biofilm support material. Higher chemical oxygen demand (COD) removal and PNSB biofilm were obtained in the N- condition. The maximum bacteriochlorophylls occurred in the N+ suspended culture (2.65 ± 0.3 µg/g), and maximum carotenoids in the N- suspended culture (3.75 ± 1 µg/g). The cellular protein content in both conditions and biomass types was between 40 % and 44 %. The polyhydroxybutyrate content was 10–12 %, except for the N+ suspended biomass condition, which was only 3.5 %. To conclude, a nitrogen-deficient biofilm-based system showed a similar bioproduct performance to other operational modes, indicating its potential to reduce costs of PNSB-produced high value-added resources, including carotenoids, SCP, and polyhydroxybutyrate while removing organics from wastewater. Other Information Published in: Biochemical Engineering Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bej.2022.108754